The covariance of multi-field perturbations, pseudo-susy and fNL - Saffin, Paul M. (IOP Publishing, 2012)
We reconsider cosmological perturbation theory for multi-component scalars, enforcing covariance in field-space, and ensuring that phyical observations are independent of field re-definitions. We use the formalism to clarify some issues in the literature, and use pseudo-supersymmetry to derive exact expressions for terms of interest.